Authoritarian vs Participatory Leadership in the Digital Era: An Analysis of the Vitality of the Governor of Lampung's Response to Public Criticism - Zeeda, Ghuvira; Rozi, Fakhrur; Supriyanto, Supriyanto (Universitas Indonesia Mandiri, 2025)
This study aimed to describe the form of the language of power of the Lampung Provincial Government towards the Bima Lampung case and describe the form of the language of knowledge of Instagram netizens towards the Bima Lampung case on Instagram social media @awbimax, @narasinewsroom, and @kuyentertainment. The research method used is a qualitative descriptive method. The data in this study are the language of power of the Lampung Provincial Government and the language of knowledge of Instagram netizens on the Bima Lampung case. Data collection techniques used observation, documentation, reading and note-taking. Data analysis techniques in this study are identification, categorization, and interpretation. The results of this study indicate that the language of power of the Lampung Provincial Government is in the form of statements that influence the way of speaking, influence the formation of knowledge, and can create or suppress certain views and opinions. Meanwhile, the form of the language of knowledge of Instagram netizens towards Bima Lampung is in the form of statements that influence the way they view the real world, and interact with others.